Coping and Quality of Life in Oncologic Patients of the Province of Nariño, Colombia (2016)
Introduction. Coping, regarded as the set of responses to stressful situations, executed to handle and neutralize them, is part of the psychological resources of human beings and it is a personal trait evidenced as intervening in terms of perceived quality of life.Objective. To determine the relationship between coping strategies and quality of life in cancer patients at different stages of their cancer condition at an oncology unit in the province of Nariño, Colombia.Materials and Methods. Cross-sectional study in a sample of 120 cancer patients attending in COEMSSANAR IPS, located in Pasto, Nariño.Results. It was observed that the most adopted type of coping was "positive attitude", followed by "positive guidance", while the least adopted ones were "anxious care" and "hopeless". As for quality of life, it is evidenced that is favorable for this population. The relationship between coping and quality of life is different for each stage of cancer. Patients with better coping are those with higher quality of life.Conclusion. A greater effort of the State and the institutions providing health services for the adoption of coping strategies in patients affected by cancer at all stages would significantly improve the quality of life of these people.